Implementation of Rain-Fed Reservoirs as an Agricultural Irrigation Solution in Kedungbenda Purbalingga Village: Penerapan Embung Tadah Hujan sebagai Solusi Irigasi Pertanian di Desa Kedungbenda Purbalingga - Sudianto; Reni Dyah Wahyuningrum; Ajeng Dyah Kurniawati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Kedungbenda Village, Purbalingga Regency, has great agricultural potential. Agriculture in Kedungbenda Village is the livelihood of most of the village population. However, the "Harja Tani" farmer group faces serious obstacles in its limited planting cycle due to a lack of access to water. Previous attempts to overcome this problem, such as drawing water from nearby rivers and drilling wells, were unsuccessful due to the long distances caused by significant elevation differences between the river and agricultural land and high operational costs. This activity aims to implement innovative rain-fed reservoirs as an agricultural irrigation solution. The method is to create rain-fed reservoirs for water storage and agricultural irrigation. The output target of this activity is a rain-fed reservoir, which can be used to store water and be used for agricultural irrigation. Based on the activity results, the rain-fed reservoir is suitable for the partners' needs because it can be used as water storage during the dry season. Apart from that, farmer groups hope to increase agricultural productivity and improve local communities' welfare. Thus, this activity supports economic growth and sustainability of the agricultural sector in Kedungbenda village.